1995
DOI: 10.1084/jem.182.6.1785
|View full text |Cite
|
Sign up to set email alerts
|

Thiols decrease human interleukin (IL) 4 production and IL-4-induced immunoglobulin synthesis.

Abstract: Summary N-Acetyl-L-cysteine (NAC) is an antioxidant precursor of intracellular glutathione (GSH), usually given in humans as a mucolytic agent . In vitro, NAC and GSH have been shown to act on T cells by increasing interleukin (IL) 2 production, synthesis and turnover of IL-2 receptors, proliferation, cytotoxic properties, and resistance to apoptosis. We report here that NAC and GSH decrease in a dose-dependent manner human IL-4 production by stimulated peripheral blood T cells and by T helper (Th) 0-and Th2-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 31 publications
6
71
1
2
Order By: Relevance
“…Likewise, the treatment of primary human T cells with NAC efficiently attenuates IL-4 expression and secretion (47,48). Our work confirms these studies and extends the regulatory principle previously identified for CD95L to the transcriptional regulation of IL-2 and IL-4 genes.…”
Section: Discussionsupporting
confidence: 78%
“…Likewise, the treatment of primary human T cells with NAC efficiently attenuates IL-4 expression and secretion (47,48). Our work confirms these studies and extends the regulatory principle previously identified for CD95L to the transcriptional regulation of IL-2 and IL-4 genes.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, it is noteworthy that systemic administration of reagents that replenish GSH, such as NAC or 2-oxothiazolidine-4-carboxylic acid, has been shown to suppress Th2-type immune response, and to reduce airway inflammation and hyper-reactivity in animal models of asthma [40,41]. These results are in line with our present results that EDC that deplete intracellular GSH in APC promote Th2 polarization and that one EDC, TBT, exacerbates airway inflammation in a murine model of asthma.…”
Section: P<001) These Results Suggest That Edc Might Exacerbate Airmentioning
confidence: 99%
“…Intracellular redox GSH levels in these immune/inflammatory cells may also effect signal transduction and activation of transcription factors and lead to elevated gene expression (e.g. of IL-8 and IL-4) [8,234]. GSH deficiency also leads to T-cell inactivation and apoptosis [235,236].…”
Section: Immune Effector Responsementioning
confidence: 99%